Effect Of Spray-dried Ethanolic Extract of Andrographis Paniculata (Burm. F.) Nees On Streptozotocin-induced Diabetic Female Rats. - Syahrin, A. S.; Amrah, S. S.; Ghan, K. L.; Lim, B.Y.; Hasenan, N.; Hasnan, J.; Mohsins, S. J. (2006)

(untitled)
The objective of this study was to evaluate the effect of commercially prepared spray-dried ethanolic extract ol Andrographis paniculafa (AP) on streptozotocin (STZ)-induced diabetic female rats. METHODOLOGY: Rats with regular estrous cycle (EC) prior to STZ induction were randomly divided into five groups. The normal (nondiabetic) and diabetic controlgroups were given vehicle [0.2 ml of 2o/o carboxyl methyl cellulose (CMC) by gavagingl daily for 6 weeks. Other diabetic groups were treated with 50, 100 and 200 mg/kg/day of AP extracts respectively. The rats' body weight (BW), fasting blood glucose and insulin level were measured; and daily, EC evaluation was perfo;.ry1e.d1 throughout the 6-week study period. At the end.olthe experiment, rats were sacrificed and their P4fprpases were removed for histological examination."RESU LTS':, The survival rates and estrous cycle,'$f''AP-treatbd diabetic animals were found to be improved compared to nontreated animals.